Avoiding anchoring bias by moving beyond ‘mechanical falls’ in geriatric emergency medicine - Nagaraj, G.; Hullick, C.; Arendts, G.; Burkett, E.; Hill, Keith; Carpenter, C. (Wiley-Blackwell Publishing Asia, 2018)
An 84 year old functionally independent man, presents with right‐sided chest pain. His general practitioner prescribed rivaroxaban 9 months ago following a deep venous thrombosis. He was cleaning his garage and slipped from a small stool, falling backwards onto his bottom and then chest. He reports three other falls over the last year, but none of them were injurious and he has not sought medical care before today. His only other past medical history is hypertension for which his general practitioner recently added a third antihypertensive agent. He has blood pressure 105/73, heart rate 96, oxygen saturation 92% on room air and Glasgow Coma Scale 15. His chest wall is tender on the right without crepitus or palpable deformity. No traumatic injuries were found on imaging. The patient is eager to return home, as you contemplate an opportunity to prevent future injurious falls. Should emergency medicine's role include intervening in this sentinel event?